The Encrypted Sermons of Sabato Morais - Cobin, David M. (Journal of law and religion, 2007)
In the course of researching the attitudes of nineteenth-century rabbis about American slavery, David Cobin found that the name Sabato Morais featured prominently among rabbis who had publicly expressed strong anti-slavery sentiments. This information sent Cobin to the American Jewish History Library where some of Morais's papers are archived to find original documents on the matter. There he found sermons from 1861 to 1862 with English script title pages and text all written in Pitman Shorthand, presumably by Morais himself. One of these, an undated document entitled The Slavery of the Bible, described as a lecture, seemed to be exactly on point. Cobin's first hurdle, however, was transcribing Morais's lecture. After a significant search he found Dorothy Roberts, who had become an expert on Civil War Pitman Shorthand specifically in order to engage in this kind of scholarly transcription. It was soon clear, however, that transcribing a more than one hundred and forty year-old shorthand written for oneself was not a simple matter. There were obsolete words, partial words, undecipherable words, words left out, references to obscure incidents, incomplete quotations, and words in multiple languages. Cobin enlisted the collaboration of his colleague Earl Schwartz as co-editor, and together they partnered in the transcription process with Dorothy Roberts. Roberts transcribed the shorthand as best she could. Cobin and Schwartz then researched the history, filled in the Judaic references and mined old dictionaries and their own imaginations for language of the times to fit the words Roberts could not fully transcribe. Roberts always made the final decision on the appropriateness of the editors' suggestions in light of the shorthand. This work yielded the transcribed lecture, The Slavery in the Bible that indeed spoke about slavery in the time of the Bible, but not about American slavery. Morais's focus was on a humane form of slavery in contrast to slavery in Sparta and Rome. Unlike Rabbi Morris Raphall's discourse on The Bible View of Slavery January 15, 1861 that was used by Southerners as a defense of slavery, Morais's lecture provided little material to fuel the conflagration then raging. The editors have concluded that Morais's lecture was likely delivered as a response to Raphall's widely publicized discourse. The Slavery of the Bible is included with the four transcribed Sabbath sermons published here.